Adenosine-Mediated Elevation of Cyclic 3′:5′-Adenosine Monophosphate Concentrations in Cultured Mouse Neuroblastoma Cells - Blume, Arthur J. (1973)
Adenosine causes an increase in the concentration of cyclic AMP in mouse neuroblastoma cells. The amount of increase observed in intracellular cyclic AMP levels due to exogenous adenosine depends greatly on the concentration of a specific cyclic AMP phosphodiesterase inhibitor, 4-(-3-butoxy-4-methoxybenzyl)-2-imidazolidinone. Unstimulated concentrations of cyclic AMP were 29-40 pmol/mg of protein, and concentrations after addition of 0.2 mM adenosine were usually twice as high. The presence of 0.7 mM inhibitor along with 0.2 mM adenosine caused an increase in cyclic AMP levels up to 1000-2000 pmol/mg of protein. In the presence of 0.7 mM inhibitor, 2 μM adenosine gives a half-maximal cyclic AMP elevation. Theophylline blocked the elevation of cyclic AMP concentrations caused by exogenous adenosine. The data show that the cyclic AMP system of mouse neuroblastoma has the necessary receptor components to respond positively to exogenous adenosine. The results presented support a direct effect of adenosine, mediated through its control of intracellular levels, on neuronal elements of the nervous system.